Business Planning : N4M Collection / Muhd Hafeez Abd Hai ...[et al.] - Abd Hai, Muhd Hafeez; Mohamad Yasin, Nuur Izzah Shahidah; Abdullah, Fasehah; Jamaludin, Nur Mazedah; Ramli, Nazirah; Ismail, Nurul Ayikin (2008)
Our company name is N4M COLLECTION and the form of our business is partnership. This company is situated in Pasir Puteh, Kelantan. This business is a service to the customer especially for student, businessman / women and people who like stylish. Our mission is very simple which is to become one of the company that will deal directly with the future athlete and any people that interested to know a lot of information about world of Islamic fashion. In the same time we also make it services is to provide all material about clothes. It is include give the information about how to choose a good clothes for our identity, give new knowledge about fashion, also try to help them that interested to wear our traditional clothes. The core objective is try to fulfill all the material that user need especially in Kelantan as we know, a country we call as “Serambi Mekah”. Following by the decision-making we are ready to start the business operation on 4th April 2008. This business will become one of the great boutique center based on the future prospect here such as sustainable and well establish among the community